2018
DOI: 10.1186/s13002-018-0208-9
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous uses of ethnomedicinal plants among forest-dependent communities of Northern Bengal, India

Abstract: BackgroundTraditional knowledge on ethnomedicinal plant is slowly eroding. The exploration, identification and documentation on utilization of ethnobotanic resources are essential for restoration and preservation of ethnomedicinal knowledge about the plants and conservation of these species for greater interest of human society.MethodsThe study was conducted at fringe areas of Chilapatta Reserve Forest in the foothills of the eastern sub-Himalayan mountain belts of West Bengal, India, from December 2014 to May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(104 citation statements)
references
References 47 publications
2
84
0
3
Order By: Relevance
“…Data were collected through personal interviews using a pretested structured questionnaire and focus group discussions (Dey et al, 2017b(Dey et al, , 2017aRaj et al, 2018;Suleiman et al, 2017). Moreover, key informants were also…”
Section: Data Collectionmentioning
confidence: 99%
“…Data were collected through personal interviews using a pretested structured questionnaire and focus group discussions (Dey et al, 2017b(Dey et al, , 2017aRaj et al, 2018;Suleiman et al, 2017). Moreover, key informants were also…”
Section: Data Collectionmentioning
confidence: 99%
“…Home gardens of Cooch Behar are smaller with an average size of 0.61 ha than that of other parts of India or elsewhere but are generally high in native diversity including ethnomedicinal plants [ 1 , 7 – 11 ]. In India, particularly in West Bengal, people living in remote and rural areas are still dependent on traditional medicines for the treatment of various ailments due to lack of modern medical facilities and poor socioeconomic conditions [ 21 27 ]. Further, the elders of the region are skeptical on the retention of traditional knowledge and advocate documentation of these old age traditions and domestication of such valuable plant species for renewed interests among new generations and cultural transmissions of this valuable knowledge system [ 14 – 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the pioneering studies on ethnobotanical study in home gardens reported only 17 species [ 22 ]. The number increased to 78 species after a decade [ 27 , 31 ]. This indicates increasing use and importance given by the local community residing in the area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Segundo RAJ et al (2018), o uso de plantas medicinais com intuito de tratar várias doenças é algo explícito que faz parte da cultura humana. O conhecimento etnomedicinal é um recurso antigo valioso para o cuidado da saúde das pessoas, sendo, portanto, um saber milenar para futura sociedade no uso sustentável e sua conservação.…”
Section: Introductionunclassified